Risk factors for sexually transmitted infections in women in rural Northeast Brazil - Fabíola Araújo Oliveira; Katrin Lang; Viola Ehrig; Jorg Heukelbach; Francisco Fraga; Marina Stoffler-Meilicke; Ralf Ignatius; Ligia Regina Franco Sansigolo Kerr; Hermann Feldmeier (Journal of Infection in Developing Countries)
Background: Sexually transmitted infections (STIs) are highly prevalent in northeast Brazil, but factors associated with the presence of an STI have rarely been studied systematically. Methodology: We performed a population-based study to assess factors associated with STIs in women of reproductive age (12 to 49 years) in a rural setting in northeast Brazil. A total of 734 women were eligible; 592 (80.7%) had initiated sexual life and were included. Women were examined for the presence of an STI. Socio-economic variables, sexual history, and behaviour were assessed through a structured questionnaire. Laboratory testing included: polymerase chain reaction for human papillomavirus (HPV); ligase chain reaction for Chlamydia trachomatis and Neisseria gonorrhoeae; VDRL and FTA-ABS for Treponema pallidum; analysis of wet mounts, gram stain and Pap smears for Trichomonas vaginalis; and ELISA for HIV. Results: At least one STI was present in 112 (19.6%) of the women. In logistic regression analysis, a previous visit to a Pap smear clinic was protective against an STI (OR=0.26; IC 95%: 0.12-0.57). The following variables were independently associated with STIs: ≥3 partners in life (2.35; 1.32-4.17); first pregnancy